Analisis Nilai-Nilai Pendidikan Islam Dalam Serial Animasi Nussa dan Rarra Produksi The Little Giantz - Salsabila, Alifia Nisa; Husna, Nihayatul (IAINU Kebumen, 2025)
As technology develops, more and more young children are starting to become addicted to gadgets. They can access anything they want, this can have a negative impact on them if they see negative content. Nussa and Rarra animations are here as a solution for positive educational content for children. For this reason, the purpose of this study is to determine the values ​​of Islamic education in Nussa and Rarra animations. This study uses a qualitative descriptive approach and takes one episode in the Nussa and Rarra animation season three as a research sample. The data collection techniques used are documentation methods and observation methods. The data analysis technique uses content analysis techniques. Based on the results of the study, it can be concluded that the Nussa and Rarra animation contains Islamic educational values. These values ​​include the value of faith in the form of an attitude of trust in Allah. The value of worship in the form of saying the sentence thayyibah. Moral values ​​include attitudes of social care, patience, honesty, hard work, sincerity, responsibility, gratitude, husnudzon, self-reflection, and obedience to parents